Bottom of The Pyramid Marketing - Sharma, Smita (Indian Journal of Marketing, 2007)
In recent years, a very few people have realized that if we stop thinking of the poor as victims or as a burden and start recognizing them as resilient and creative entrepreneurs and value conscious consumers, a whole new world of opportunity will open up. There has been an assumption that the rich will be served by corporate sector, while government and NGOs will protect the poor and the environment. If we talk of a revolutionary proposition of serving low-income markets, how many marketers are ready to accept this? The Bottom of Pyramid is a new management concept that conveys the promise to fulfill a twofold objective: promote social development and allow companies to regain double-digit growth rates. The emergence of a huge population who make up the Tier 4 market is a great opportunity for MNCs. It also represents a chance for business, government, and civil society to join together in a common cause. There's a huge opportunity lying for linking the poor and the rich across the world in a seamless market organized around the concept of sustainable growth and development. Selling to the poor-the base of the pyramid-is a key part of the economy and an important aspect of social existence. There have been initiatives by many companies in reaching the poorest of the poor in India and other developing countries. For instance, "single-serve revolution" is sweeping poor countries, as companies learn to sell small packets of shampoo, ketchup, tea, coffee or aspirin. Tier 4 is becoming aware of many products and services and is aspiring to share the benefits. The poor cannot participate in the benefits of globalization without an active involvement of the private sector and without access to products and services that represent global quality standards. Are we all ready to explore "Bottom of Pyramid"?